Determination of mechanical properties of traditiona masonry walls in dwellings of Faial Island, Azores. - Costa, Anibal (Earthquake engineering & structural dynamics.)
The determination of mechanical properties of masonry walls is a fundamental pre-requisite for the characterization of the seismic response of traditional buildings, which helps on the definition of adequate rehabilitation and strengthening procedures. This paper presents a testing campaign carried out in the Cedros region of Faial Island, Azores, hit by the July 98 earthquake, aiming at the determination of physical and mechanical properties of stone masonry walls, namely the mass density and Young's modulus. The paper describes the developed testing techniques as a contribution to the study and the preservation of traditional masonry buildings.